Fertilizer micro-dosing increases crop yield in the Sahelian low-input cropping system: a success with a shadow - Ibrahim, A.; Abaidoo, Robert C.; Fatondji, D.; Opoku, A. (Informa UK Limited, 2016)
Over the years, a scarcity of information on nutrient gains or losses has led to overemphasis being placed on crop yields and economic income as the direct benefits from fertilizer micro-dosing technology. There is increasing concern about the sustainability of this technology in smallholder Sahelian cropping systems. This study was designed in the 2013 and 2014 cropping seasons to establish nutrient balances under fertilizer micro-dosing technology and their implications on soil nutrient stocks. Two fertilizer micro-dosing treatments [2 g hill−1 of diammonium phosphate (DAP) and 6 g hill−1 of compound fertilizer Nitrogen-Phosphorus-Potassium (NPK) (15-15-15)] and three rates of manure (100 g hill−1, 200 g hill−1 and 300 g hill−1) and the relevant control treatments were arranged in a factorial experiment organized in a randomized complete block design with three replications. On average, millet (Pennisetum glaucum (L.) R.Br.) grain yield increased by 39 and 72% for the plots that received the fertilizer micro-dosing of 6 g NPK hill−1 and 2 g DAP hill−1, respectively, in comparison with the unfertilized control plots. The average partial nutrients balances for the two cropping seasons were −37 kg N ha−1yr−1, −1 kg P ha−1yr−1 and −34 kg K ha−1yr−1 in plots that received the application of 2 g DAP hill−1, and −31 kg N ha−1yr−1, −1 kg P ha−1yr−1 and −27 kg K ha−1yr−1 for 6 g NPK hill−1. The transfer of straw yields accounted for 66% N, 55% P and 89% K for removal. The average full nutrient balances for the two cropping seasons in fertilizer microdosing treatments were −47.8 kg N ha−1 yr−1, −6.8 kg P ha−1 yr−1 and −21.3 kg K ha−1 yr−1 which represent 7.8, 24.1 and 9.4% of N, P and K stocks, respectively. The nutrient stock to balance ratio (NSB) for N decreased from 13 to 11 and from 15 to 12 for the plots that received the application of 2 g DAP hill−1 and 6 g NPK hill−1, respectively. The average NSB for P did not exceed 5 for the same plots. It was concluded that fertilizer micro-dosing increases the risk of soil nutrient depletion in the Sahelian low-input cropping system. These results have important implications for developing an agro-ecological approach to addressing sustainable food production in the Sahelian smallholder cropping system.